Evidence of decrease of potential energy in nonsequential double ionization above threshold for electron impact excitation - Chen, Zhangjin; Lin, C. D. (My University, 2014)
We study the CEP (carrier envelope phase) dependent correlated electron momentum distributions for nonsequential double ionization of Ar in near-single-cycle short pulses at the intensity of 3.0 × 1014 W/cm2 with a central wavelength of 750 nm measured by Bergues et al [Nat. Comm. 3, 813 (2012)]. A kinematical analysis on the constraints for the correlated electron momenta reveals that the excitation potentials of the parent ion Ar+ are reduced at the instant of scattering.